Association between ADIPOQ G276T and C11377G polymorphisms and the risk of non‐alcoholic fatty liver disease: An updated meta‐analysis. Issue 5 (5th March 2019) - Liu, Mengwei; Liu, Shan; Shang, Mengke; Liu, Xiuping; Wang, Yue; Li, Qian; Mambiya, Michael; Yang, Luping; Zhang, Qian; Zhang, Kaili; Nie, Fangfang; Zeng, Fanxin; et al.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a significant contributor to global hepatic disorders. ADIPOQ gene single‐nucleotide polymorphisms have been associated with NAFLD susceptibility, but with inconsistent results across the studies. This study aimed to investigate the association between ADIPOQ polymorphisms (+276G>T, rs1501299 and −11377C>G, rs266729) and the risk of NAFLD. Methods: PubMed, Embase, Wanfang, Web of Science, and China National Knowledge Infrastructure databases were used to identify the relevant published literature. Statistical analyses were calculated with STATA 11.0 software and RevMan 5.2. Summary odds ratios (OR) and 95% confidence intervals (CIs) were generated to assess the strength of the associations. Results: Eleven relevant articles with a total of 3, 644 participants (1, 847 cases/1, 797 controls) were included. Our meta‐analysis results revealed that ADIPOQ gene +276G>T polymorphism was not associated with NAFLD under various genetic models (allele model: OR = 0.99, 95% CI [0.69, 1.41]; dominant model: OR = 1.06, 95% CI [0.71, 1.58]; recessive model: OR = 0.83, 95% CI [0.42, 1.65]; homozygous model: OR = 0.86, 95% CI [0.38, 1.95]; heterozygous model: OR = 1.10, 95% CI [0.80, 1.53]; respectively). Moreover, no statistical significant association was found between +276G>T and NAFLD risk in the subgroups. ADIPOQ gene −11377C>G polymorphism significantly increased the risk of NAFLD (allele model: OR = 1.49, 95% CI [1.28, 1.75]; dominant model: OR = 1.64, 95% CI [1.35, 1.99]; recessive model: OR = 1.77, 95% CI [1.16, 2.70]; homozygous model: OR = 2.13, 95% CI [1.38, 3.28]; heterozygous model: OR = 1.58, 95% CI [1.29, 1.93]; respectively). Conclusion: ADIPOQ gene −11377C>G may be a risk factor for NAFLD, while there was no association between ADIPOQ gene +276G>T polymorphism and the risk of NAFLD. Further studies are needed to detect the relationship between these ADIPOQ polymorphisms and NAFLD. Abstract : Nonalcoholic fatty liver disease (NAFLD) is a significant contributor to global hepatic disorders. ADIPOQ gene single‐nucleotide polymorphisms (SNPs) have been associated with NAFLD susceptibility, but with inconsistent results across the studies. The results indicated that ADIPOQ gene −11377C>G may be a risk factor for NAFLD, while there was no association between ADIPOQ gene +276G>T polymorphism and the risk of NAFLD. Flow diagram of the study search and selection process.